Adsorption of Thiocyanate Anions from Aqueous Solution onto Adsorbents of Various Origin - Noelia V. Aguirre; Beatriz Padilla Vivas; Miguel A. Montes-Morán; Conchi O. Ania (Adsorption Science & Technology)
The removal of thiocyanate, a toxic anion originating in a large number of industrial processes, from aqueous solutions was investigated using adsorbents of different natures (activated carbon, zeolite, diatomite, sepiolite, hydrotalcite, steel-making residues). The uptake of thiocyanate anions did not seem to be directly related to the porous features of the adsorbents, but rather connected to the ion–adsorbent affinity. The highest retention in synthetic solutions was obtained with hydrotalcite, followed by activated carbon, zeolite and the steel-making slags. In real wastewater, the removal efficiency of hydrotalcite relative to industrial wastewater was largely suppressed due to the organic matter present. In contrast, the retention ability of the activated carbon and the slags was less modified in real wastewater due to their open porous networks. These results indicate that steel-making slag could be used as a potential adsorbent for the removal of thiocyanate anions from real wastewater produced in coke-making processes without any additional processing.